Analysis of Renewable Energy, Foreign Direct Investment, and CO2 Relationship: Evidence from France, Germany, and Italy - Akbulaev, Nurkhodzha (International Journal of Energy Economics and Policy, 2023)
Transitions to renewable energy sources have begun in several countries in an effort to decrease the impact of solid fossil waste. The paper examines the connection between renewable energy consumption, FDI, and CO2 emissions using econometric analysis of data from France, Germany, and Italy. The purpose of this research is to examine the correlation between the use of renewable energy sources, FDI, CO2 emissions from energy sources, and GDP growth in France, Germany, and Italy from 1971 to 2021. The data is analysed using many different tests, including those for stationarity, Granger causality, and the Toda-Yamamoto method. According to the findings, the utilisation of renewable energy sources is a driving factor in cutting CO2 emissions in France, whereas in Italy, emissions are the result of foreign direct investment. In Germany and Italy, the lack of a correlation between consumption of renewable energy, FDI, and CO2 emissions over the long term suggests that renewable energy does not play a significant role in driving economic development in those countries. Our results add to the existing body of knowledge and imply that investments in renewable energy are crucial to achieving sustainable development. Governments should take action to mitigate the negative effects of FDI on the environment and promote investments in renewable energy.